PENYULUHAN PENGGUNAAN BENIH BERMUTU DAN BERSERTIFIKAT DI PAYABENUA MENDO BARAT KABUPATEN BANGKA - Kartika Kartika (LOGISTA - Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Penggunaan benih bermutu dan bersertifikat adalah langkah awal untuk meningkatkan produktivitas dalam suatu usaha pertanian. Permasalahannya, persepsi dan apresiasi petani terhadap benih bermutu dan bersertifikat masih sangat beragam. Oleh karena itu diperlukan kegiatan penyuluhan untuk memberikan wawasan dan pemahaman kepada para petani tentang benih bermutu dan bersertifikat didalam usaha pertanian. Kegiatan penyuluhan terkait benih bermutu dan bersertifikat dilakukan dalam kegiatan Kuliah Kerja Nyata Tematik di Desa Payabenua Kabupaten Bangka. Kegiatan tersebut dihadiri oleh petani dan masyarakat. Narasumber berasal dari Balai Pengawasan dan Sertifikasi Mutu Benih dan Balai Pengkajian Teknologi Pertanian Provinsi Kepulauan Bangka Belitung. Digunakan kuisioner untuk mengetahui respon petani setelah mengikuti kegiatan penyuluhan. Persepsi dan apresiasi petani di desa Payabenua berubah setelah mengikuti penyuluhan. Para petani yang awalnya belum menggunakan benih bermutu dan bersertifikat setelah mengikuti kegiatan penyuluhan akan menggunakan benih bermutu dan bersertifikat untuk kegiatan usaha taninya. Terdapat kendala di petani untuk dapat mengakses benih bermutu dan bersertifikat yaitu terkait harga dan kesesuaian varietas. Perlu dilakukan kegiatan penyuluhan yang terjadwal dan rutin agar wawasan petani yang bertambah dapat diikuti dengan pemahaman tentang pentingnya benih bermutu dan bersertifikat. Kata kunci: Payabenua, persepsi, apresiasi ABSTRACT The use of quality and certified seeds is the first step to increase productivity in an agricultural business. The problem is that farmers' perceptions and appreciation of quality and certified seeds are still very diverse. Therefore extension activities are needed to provide insight and understanding to farmers about quality and certified seeds in agricultural business. Counseling activities related to quality and certified seeds were carried out in the Thematic Real Work Lecture activities in Payabenua Village, Bangka Regency. The activity was attended by farmers and the community. The resource persons came from the Center for Supervision and Certification of Seed Quality and the Center for Agricultural Technology Studies of the Bangka Belitung Islands Province. Questionnaires were used to find out the response of farmers after participating in counseling activities. The perception and appreciation of farmers in Payabenua village changed after attending counseling. Farmers who initially did not use quality and certified seeds after participating in extension activities will use quality and certified seeds for their farming activities. There are obstacles for farmers to be able to access quality and certified seeds, namely related to price and suitability of varieties. It is necessary to carry out scheduled and routine extension activities so that farmers' increased insight can be followed by an understanding of the importance of quality and certified seeds. There are obstacles for farmers to be able to access quality and certified seeds, namely related to price and suitability of varieties. It is necessary to carry out scheduled and routine extension activities so that farmers' increased insight can be followed by an understanding of the importance of quality and certified seeds. There are obstacles for farmers to be able to access quality and certified seeds, namely related to price and suitability of varieties. It is necessary to carry out scheduled and routine extension activities so that farmers' increased insight can be followed by an understanding of the importance of quality and certified seeds. Keywords: Payabenua, quality seeds, perceptions, appreciation